Identification of quantitative trait loci associated with soybean seed protein content using two populations derived from crosses between Glycine max and Glycine soja. (16th July 2014) - Yan, Long; Xing, Li-Li; Yang, Chun-Yan; Chang, Ru-Zhen; Zhang, Meng-Chen; Qiu, Li-Juan
Abstract : Seed protein content is one of the most important traits controlled by quantitative trait loci (QTLs) in soybean. In this study, a Glycine soja accession (ZYD2738) was crossed with two elite cultivars Jidou 12 and Jidou 9 separately and subsequently the resulting F2:3 populations were used to identify QTLs associated with seed protein content. Protein contents in either population appeared to have a normal distribution with transgressive segregation. A total of five QTLs associated with high protein content were identified and mapped to chromosomes 2, 6, 13, 18 and 20, respectively. Of these QTLs, three ( qPRO_2_1, qPRO_13_1 and qPRO_20_1 ) were identified in the same region in both the populations, whereas the other two ( qPRO_6_1 and qPRO_18_1 ) were mapped in two different regions. qPRO_2_1 appears to be a novel protein QTL. qPRO_6_1, qPRO_18_1 and qPRO_20_1 had additive effects on seed protein content, while qPRO_13_1 had an over-dominant effect on seed protein content. These QTLs and their linked markers could serve as effective tools for marker-assisted selection to increase seed protein content.